Proteome Profiling of RNF213 Depleted Cells Reveals Nitric Oxide Regulator DDAH1 Antilisterial Activity - Martina, Lia; Asselman, Caroline; Thery, Fabien; Boucher, Katie; Delhaye, Louis; Maia, Teresa M.; Dermaut, Bart; Eyckerman, Sven; Impens, Francis (Frontiers in Cellular and Infection Microbiology, 2021)
RNF213 is a large, poorly characterized interferon-induced protein. Mutations in RNF213 are associated with predisposition for Moyamoya disease (MMD), a rare cerebrovascular disorder. Recently, RNF213 was found to have broad antimicrobial activity in vitro and in vivo, yet the molecular mechanisms behind this function remain unclear. Using mass spectrometry-based proteomics and validation by real-time PCR we here report that knockdown of RNF213 leads to transcriptional upregulation of MVP and downregulation of CYR61, in line with reported pro- and anti-bacterial activities of these proteins. Knockdown of RNF213 also results in downregulation of DDAH1, which we discover to exert anti-microbial activity against Listeria monocytogenes infection. DDAH1 regulates production nitric oxide (NO), a molecule with both vascular and antimicrobial effects. We show that NO production is reduced in macrophages from RNF213 KO mice, suggesting that RNF213 controls Listeria infection through regulation of DDAH1 transcription and production of NO. Our findings propose a potential mechanism for the antilisterial activity of RNF213 and highlight NO as a potential link between RNF213-mediated immune responses and the development of MMD.